O efeito da suplementação com creatina sobre o deficit cognitivo induzido pelo traumatismo cranioencefálico em ratos jovens - Busanello, Guilherme Lago (2015)
By definition Traumatic brain injury (TBI) is a common involvement in all societies and covers the entire set of processes that alone or in combination can damage the brain. In children and adolescents TBI is an interruption in their normal development, with estimates ranging from 200 to 500 cases per 100,000 per year. Most cases are characterized as mild, with few long-term consequences, however, a significant portion of young people suffer more serious injuries. Furthermore, Juvenile TBI is the major cause of death and disability in children and adolescents. An important factor is that the sports and youth have always been closely related. In this sense, it called attention traumas, especially for young people during practice of contact sports such as martial arts, football, ice hockey, baseball. Because of the wide variety of conditions associated with TBI, there is considerable interest in the development and subsequent application of biochemical markers that relate the severity of brain damage with the development of neurological problems such as memory and learning deficits. In this context, this study aimed, at first, to see if the young animals subjected to TBI had cognitive impairment fifteen days after the injury and whether creatine supplementation has protective effect by changing the activity of CK enzyme, modulating the expression of AMPK protein, CREB, p-CREB and BDNF involved in cognitive impairment and histological damage generated by TBI To this end the present study used young male Wistar rats at 35 days of life subjected to TBI or subjected to all processes except TBI were divided into four groups which were randomized to receive the Cr supplementation (300 mg / kg po) was suspended in 0.5% CMC or vehicle (CMC) twice daily for a period of 14 days. it was shown that animals on submitted to TBI showed a reduction in cognitive functions evaluated by 15 days object recognition task after TBI. The animals that received creatine supplementation did not have their compromised functions. Our biochemical data revealed that the activity of the enzyme creatine kinase was increased fifteen days after trauma, in the same period the TBI did not alter the expression of AMPK however creatine supplementation increased its expression, suggesting a connection between CK and AMPK after TBI, since the creatine supplementation was effective in raising the activity of CK while increased expression of AMPK also caused a significant increase in the ratio of CREB and p-CREB in animals that were supplemented. We also note the participation of BDNF, whose expression this increases the animals submitted to the TBI and were supplemented with creatine, protection evidenced by creatine in lesion volume induced by the TBI.